Socio-cultural implications for women's menstrual health in the Pacific Island Countries and Territories (PICTs): a scoping review - Elizabeth Maulingin-Gumbaketi; Sarah Larkins; Maxine Whittaker; Gun Rembeck; Ronny Gunnarsson; Michelle Redman-MacLaren (BMC, 2022)
Plain language Summary Globally, menarche is an important developmental milestone for females. Experiences of menarche and subsequent menstruation are embedded in socio-cultural norms and practices which can impact women's ability to manage menstruation with dignity. This paper reviews social and cultural factors that affect the ability of women to effectively manage their menstrual health and hygiene (MHH) in Pacific Island Countries and Territories (PICTs). Peer-reviewed and grey literature were searched systematically, using the PRISMA extended scoping review methodology. Eleven studies met the inclusion and exclusion criteria: 10 qualitative studies and one mixed methods study. Included studies had been conducted in Melanesian (n = 9), Polynesian (n = 1) and Micronesian (n = 1) states of PICTs. Factors affecting MHH were identified and categorised using the Socio-Ecological Framework categories: biological; personal; interpersonal; environmental and societal. All 11 studies reported elements of societal and personal factors; ten studies reported evidence relating to interpersonal factors; nine studies reported elements relating to environmental factors; and two studies presented evidence linked to biological factors. MHH experiences of women in PICTs are shaped by socio-cultural norms and practices. These norms and practices need to be incorporated into sexual and reproductive health planning, programs and education in order to be relevant to diverse village and urban settings in PICTs.